Producing multi-coloured bunches through beam-induced ionization injection in plasma wakefield accelerator. (24th June 2019) - Vafaei-Najafabadi, N.; Amorim, L. D.; Adli, E.; An, W.; Clarke, C. I.; Clayton, C. E.; Corde, S.; Gessner, S.; Green, S. Z.; Hogan, M. J.; Joshi, C.; Kononenko, O.; et al.
Abstract : This paper discusses the properties of electron beams formed in plasma wakefield accelerators through ionization injection. In particular, the potential for generating a beam composed of co-located multi-colour beamlets is demonstrated in the case where the ionization is initiated by the evolving charge field of the drive beam itself. The physics of the processes of ionization and injection are explored through OSIRIS simulations. Experimental evidence showing similar features are presented from the data obtained in the E217 experiment at the FACET facility of the SLAC National Laboratory. This article is part of the Theo Murphy meeting issue 'Directions in particle beam-driven plasma wakefield acceleration'.